2018
DOI: 10.1051/0004-6361/201731951
|View full text |Cite
|
Sign up to set email alerts
|

A 1.3 mm SMA survey of 29 variable young stellar objects

Abstract: Context. Young stellar objects (YSOs) may undergo periods of active accretion (outbursts), during which the protostellar accretion rate is temporarily enhanced by a few orders of magnitude. Whether or not these accretion outburst YSOs possess similar dust/gas reservoirs to each other, and whether or not their dust/gas reservoirs are similar as quiescent YSOs, are issues not yet clarified. Aims. The aim of this work is to characterize the millimeter thermal dust emission properties of a statistically significan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 129 publications
4
36
0
Order By: Relevance
“…Spectral indices < 2 have indeed been reported several times in the literature (Jørgensen et al 2009;Miotello et al 2014;Li et al 2017;Liu et al 2018). Sometimes they have been attributed to calibration errors, very low dust temperatures (e.g., Hirano & Liu 2014), or a significant contribution of free-free emission .…”
Section: (Sub)millimeter Spectral Indices From Model Gridssupporting
confidence: 54%
See 1 more Smart Citation
“…Spectral indices < 2 have indeed been reported several times in the literature (Jørgensen et al 2009;Miotello et al 2014;Li et al 2017;Liu et al 2018). Sometimes they have been attributed to calibration errors, very low dust temperatures (e.g., Hirano & Liu 2014), or a significant contribution of free-free emission .…”
Section: (Sub)millimeter Spectral Indices From Model Gridssupporting
confidence: 54%
“…However, it is not clear to which extent selfscattering can dominate over magnetic-field alignment in the polarized emission (e.g., Lee et al 2018;Girart et al 2018). It is possible that in class 0 and I protostars magnetic fields tend to dominate (Alves et al 2018;Liu et al 2018). We conclude that self-obscuration due to relatively high masses and temperature structure could be an important part of the puzzle, helping to explain low spectral indices without needing to invoke significant dust evolution at the earliest YSO stages.…”
Section: Normalized Countsmentioning
confidence: 82%
“…Moreover, this explains how the 0.1-0.3 au scale hot inner disk with a 10 −4 M e yr −1 mass accretion rate (see Section 4.1) is being replenished by the up to ∼10 au scale gas reservoir at a modest rate, such that the hot inner disk neither becomes depleted nor accumulates mass over a short timescale. This may explain the relatively stable mid-infrared and (sub) millimeter fluxes in the previous monitoring observations (Green et al 2016a;Liu et al 2018).…”
Section: Outbursting Versus Quiescent Disks?mentioning
confidence: 67%
“…The outbursts clear the material surrounding the star, helping the transition from the embedded Class I to disk-only Class II. Recent studies have shown that FUor disks are smaller and more massive than previously thought (Cieza et al 2018, andLiu et al 2018).…”
Section: Introductionmentioning
confidence: 81%